Sierra Leone : Ad Hoc Review Under the Extended Credit Facility Arrangement and Request for Augmentation of Access, Modification of Performance Criteria, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Background. The Ebola outbreak that started in one district in late May has spread to the entire country, overwhelming already weak institutions and ill-equipped medical facilities. At end-August, over 1000 people were infected and more than a third had died from the disease. The country's social and economic fabric is also adversely affected by the epidemic. Economic growth has slowed, inflationary pressures have intensified, and new balance of payments and fiscal financing needs have emerged. The epidemic has heightened food insecurity and impacted livelihoods for a large portion of the population, generating additional distress for vulnerable groups. The program. In October 21, 2013, the Executive Board approved a three-year arrangement under the Extended Credit Facility (ECF) for Sierra Leone totaling SDR 62.2 million (60 percent of quota). The first review under the program was completed on June 19, 2014. Preliminary indications are that performance under the program is on track, in spite of weaknesses in budget execution at end-June. The authorities' requests. In the attached letter of intent, the Sierra Leone authorities are requesting an Ad Hoc review under the ECF arrangement, and an augmentation of access in an amount equivalent to 25 percent of quota (SDR 25.925 million), in a single disbursement. These resources, together with contributions from other donors will help cover balance of payments and budgetary financing needs generated by the Ebola epidemic. The authorities are also requesting a modification of end-December 2014 performance criteria on net domestic bank credit to the central government, and on net domestic assets of the central bank. Safeguard assessment. A safeguards assessment of the Bank of Sierra Leone (BoSL) was completed in March 2014. The BoSL is taking steps to strengthen its safeguards framework and staff is monitoring implementation of the recommendations from the assessment. Staff views. Staff supports the completion of the Ad Hoc review, and the authorities' requests.